MAKNA SIMBOLIK GERAKAN TARIAN SUFI TURKI JALALUDIN RUMI (1203-1273M): ANALISIS SEMIOTIKA CHARLES SANDER PIERCE - Razqan Anadh Mahendar (Arabic Literature Department, 2014)
This research discussed : (1) How the sufi dance lasts? (2) What is thesymbolic meaning of sufi dance movements and it‟s message that wanted to bedelivered ? This research used qualitative method which is presented descriptively bydescribe Sufism in general, Sufism flow, Sufism development, describe Sufidance in term of it‟s development, symbolic meaning are the meaning of sufidance movement and the clothing which were worn by the sufi dancers. Based on the result of this research conclude are : first, sufi dance is identicwith Sufism and the figures who influence this dance. Second, sufi dancemovements have a message that wanted to be delivered to everyone. Third, sufidance has a function as syi‘ar of Islam.